Data to Physicalization: A Survey of the Physical Rendering Process. (29th June 2021) - Djavaherpour, H.; Samavati, F.; Mahdavi‐Amiri, A.; Yazdanbakhsh, F.; Huron, S.; Levy, R.; Jansen, Y.; Oehlberg, L.
Abstract: Physical representations of data offer physical and spatial ways of looking at, navigating, and interacting with data. While digital fabrication has facilitated the creation of objects with data‐driven geometry, rendering data as a physically fabricated object is still a daunting leap for many physicalization designers. Rendering in the scope of this research refers to the back‐and‐forth process from digital design to digital fabrication and its specific challenges. We developed a corpus of example data physicalizations from research literature and physicalization practice. This survey then unpacks the "rendering" phase of the extended InfoVis pipeline in greater detail through these examples, with the aim of identifying ways that researchers, artists, and industry practitioners "render" physicalizations using digital design and fabrication tools.